Development and potential environmental impact of Photonic Meta-Concrete. Issue 1 (1st September 2022) - Adams, N; Allacker, K; Dolado, J S
Abstract: In the overall aim to reduce the heat-island-effect in cities and the related use of conventional air-conditioners, which now account for 7% of global greenhouse gas emissions and 10% of the total energy consumption, a Photonic Meta-Concrete (PMC) is currently being developed. This "MIRACLE" concrete is designed to contain remarkable photonic properties to make daytime radiative cooling possible. With these characteristics, the PMC can be used to fight global warming, reduce the CO2 footprint and mitigate the heat-island-effect. This paper describes the principal working of the new PMC and presents the first results of the development. In the first stage, the most appropriate composition of the concrete mixture is searched for. This is done by trying to develop a mixture with the desired photonic properties, a high emissivity in the Atmospheric Window (AW) and a high reflectivity to minimize solar gains. A range of composites are tested and compared within this step. Secondly, an environmental impact assessment (EIA) study is performed along the development of the PMC in order to support decision taking. The resources and energy needed to create the concrete mixture are analysed from cradle-to-gate and a comparison with conventional concrete is made to investigate the impact of this new material. This EIA study is performed according to the EC PEF (Product Environmental Footprint) method, a broad set of indicators are assessed, including climate change. Considering such a large set of indicators ensures that burden shifting is avoided.